Institutional collaboration and shared learning for forest management in Chivi Distict, Zimbabwe - Nemarundwe, N. (Center for International Forestry Research, 2001)
This chapter examines processess of collaboration among institutions for communal woodland managemnet at the local level in Zimbabwe and explores how these processess influence sustainable resources utilization. The author discusses how institutions adapt to changing social and environmental conditions. Based on case study evidence, I argue that community-based natural resource management works best in a context of institutional collaboration and shared learning. The author identifies three requirements for collaboration: the need for effective facilitation of experimental learning, equal power in learning process and the willingness to engage in multi-stage process that can be costly.